The Effect of Trust in Government and Perceptions of Tax Justice on Tax Compliance with Job Type as Moderation (Empirical Study on Individual Taxpayers Registered at Jayapura Primary Tax Service Office) - Tuhumena, Ruland; Falah, Syaikhul; Salle, Hesty T. (AIBPM Publisher, 2023)
This study aims to analyze and provide empirical evidence of the effect of trust in government and perceptions of tax justice on tax compliance with job type as moderation at the Jayapura Primary Tax Service Office. The population in this study amounted to 100 respondents with the sampling method, namely non-probability sampling with convenience sampling technique. The data analysis method used is the Structural Equation Model (SEM) approach with the Partial Least Square (PLS) method. The test results of this study indicate that: 1) trust in government has a positive and significant effect on tax compliance, perceptions of tax justice have a positive and significant effect on tax compliance, 3) job type has not been able to moderate the effect of trust in government on tax compliance, and 4) job type has not been able to moderate the effect of perceptions of tax justice on tax compliance.